2016
DOI: 10.1007/s00330-016-4547-4
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging before transcatheter aortic valve implantation (TAVI) using variable helical pitch scanning and its diagnostic performance for coronary artery disease

Abstract: • TAVI-planning CT using variable helical pitch (VHP) scanning is useful. • The average volume of contrast material was 38.7 ± 8.5 mL. • The average attenuations of all the arteries were >400 HU. • This CT had a high sensitivity and NPV for excluding obstructive CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 22 publications
4
36
1
Order By: Relevance
“…Harris et al [37] and Matsumoto et al [38], obtained a mean CCS, respectively, similar than us, but they did not stratified the CT diagnostic performance based on CCS values. Rossi et al [39] using a second generation DSCT with a retrospective ECG-gated protocol, stratified the CT diagnostic performance using the same CCS threshold than in our study (low < 400, high ≥400), and they obtained a CT performance slightly lower than us concluding that in patients with CCS ≥ 400 CT performed less well.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Harris et al [37] and Matsumoto et al [38], obtained a mean CCS, respectively, similar than us, but they did not stratified the CT diagnostic performance based on CCS values. Rossi et al [39] using a second generation DSCT with a retrospective ECG-gated protocol, stratified the CT diagnostic performance using the same CCS threshold than in our study (low < 400, high ≥400), and they obtained a CT performance slightly lower than us concluding that in patients with CCS ≥ 400 CT performed less well.…”
Section: Discussionmentioning
confidence: 45%
“…Several previous studies [33][34][35][36][37][38][39][40] have looked to evaluate the diagnostic performance of coronary tree assessment in CT before TAVI planning and concluded that CT is a useful test to rule out significant obstructive CAD and to evaluate stents and CABGs patency. To the best of our knowledge, the present study is the work with the largest simple size and a prospective design with this aim and the only one that used a single prospective ECG-gated ultra-high pitch acquisition for aorta, iliac vessels and coronary artery assessments.…”
Section: Discussionmentioning
confidence: 99%
“…This difference is attributable to the high pitch and low CM dose, which led to a repeat acquisition in 1 of the 40 study patients due to poor image quality. Finally, while one group of researchers previously conducted a study investigating the effectiveness of preprocedural TAVI/TAVR CT using vHP and reported a radiation dose of 1281.6 ± 195.7 mGy*cm [19], to the best of our knowledge, our study is the first to demonstrate the usefulness of the novel 3-phase vHP3 in patients scheduled for TAVI/TAVR. Compared to the studies by Ippolito et al, Talei Franzesi et al, and Bittner et al, a possible concern regarding our study is that we administered higher volumes of CM (99.3 ± 22.6 ml in Group A and 105.5 ± 17.6 ml in Group B).…”
Section: Discussionmentioning
confidence: 81%
“…However, improve-ments in the design of TAVI/TAVR and an increase in operator experience have improved procedure safety, leading to an expansion of indications for the procedure into low-risk groups without age restriction, such as in the PARTNER 3 trial[19][20][21][22][23]. As a result, the need to minimize radiation exposure during preprocedural TAVI/TAVR CT while ensuring diagnostic image quality is gaining importance.…”
mentioning
confidence: 99%
“…Accurate analysis of CT scan data has shown a high sensitivity and negative predictive value in excluding obstructive coronary artery disease, thus avoiding the need for preprocedural angiographic examination in TAVI candidates with nonobstructive disease at preprocedural CT scan. 17,18 Not surprisingly, patient's age resulted inversely correlated with total exposure, meaning that younger patients are those receiving greater doses. Our data demonstrate that a reduction of 10 years in age corresponds to a 30% increase of the log-dose, thus with a potential detrimental long-term effect for younger patients.…”
Section: Discussionmentioning
confidence: 99%